2015
DOI: 10.1080/10408398.2012.749208
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Iron and Colorectal Cancer Risk: A Review of Human Population Studies

Abstract: Iron is an essential micronutrient that is involved in many redox processes and serves as an integral component in various physiological functions. However, excess iron can cause tissue damage through its pro-oxidative effects, potentiating the development of many diseases such as cancer through the generation of reactive oxidative species. The two major forms of iron in the diet are heme and nonheme iron, both of which are found in several different foods. In addition to natural food sources, intake of nonhem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 59 publications
0
23
0
Order By: Relevance
“…High dietary iron intake or patients with iron overload have increased risk for CRC (Cross et al, 2010; Osborne et al, 2010). Patients with lower iron or in mouse models treated with low iron diet exhibit a decrease in CRC (Ashmore et al, 2015; Bastide et al, 2015; Nelson, 2001). The majority of previously described mouse genetic models of intestinal tumorigenesis mainly develop small intestinal adenoma (Johnson and Fleet, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…High dietary iron intake or patients with iron overload have increased risk for CRC (Cross et al, 2010; Osborne et al, 2010). Patients with lower iron or in mouse models treated with low iron diet exhibit a decrease in CRC (Ashmore et al, 2015; Bastide et al, 2015; Nelson, 2001). The majority of previously described mouse genetic models of intestinal tumorigenesis mainly develop small intestinal adenoma (Johnson and Fleet, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have indeed shown a correlation between the incidence and mortality of cancer and systemic iron levels, as measured by transferrin saturation or serum ferritin, this correlation is generally not strong, has shown conflicting outcomes, and it is often confounded by the presence of other pathology88,89. There is, however, clear evidence that deregulated iron homeostasis on a local — that is, microenvironmental and/or cellular — level is associated with tumour progression, as illustrated by changes in expression of iron-related genes in cancer cells (Figure 4), the levels of which are inversely correlated with patient survival9092.…”
Section: Iron and The Pathophysiology Of Diseasementioning
confidence: 99%
“…Thus, haem iron content in red meat products, including processed products, was suggested as an important carcinogenic parameter contributing to the associations found in epidemiologic studies (Bastide et al 2016). An association between colorectal cancer risk and intake of iron, in particular haem iron, has been shown in several, but not all, epidemiologic studies (Ashmore et al 2016). The epidemiological studies on the carcinogenic effects of haem iron are conflicting.…”
Section: Haem Ironmentioning
confidence: 99%